2011
DOI: 10.1002/bem.20664
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of 3 T magnetic resonance imaging in cultured human lymphocytes

Abstract: The clinical and preclinical use of high-field intensity (HF, 3 T and above) magnetic resonance imaging (MRI) scanners have significantly increased in the past few years. However, potential health risks are implied in the MRI and especially HF MRI environment due to high-static magnetic fields, fast gradient magnetic fields, and strong radiofrequency electromagnetic fields. In this study, the genotoxic potential of 3 T clinical MRI scans in cultured human lymphocytes in vitro was investigated by analyzing chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 39 publications
(35 reference statements)
2
40
0
2
Order By: Relevance
“…The study of Szerencsi et al 21 showed no enhancement immediately following in vitro exposure of human leukocytes. In contrast, statistically significant enhancements were observed by Lee et al 19 following in vitro exposure times of 45 min or greater, with the observed level increasing with duration of exposure. For in vivo exposures, Yildiz et al 20 observed no significant increase in lymphocytes taken after the initial non-contrast-enhanced MRI.…”
Section: Does Mri Exposure Lead To Dna Damage?mentioning
confidence: 59%
“…The study of Szerencsi et al 21 showed no enhancement immediately following in vitro exposure of human leukocytes. In contrast, statistically significant enhancements were observed by Lee et al 19 following in vitro exposure times of 45 min or greater, with the observed level increasing with duration of exposure. For in vivo exposures, Yildiz et al 20 observed no significant increase in lymphocytes taken after the initial non-contrast-enhanced MRI.…”
Section: Does Mri Exposure Lead To Dna Damage?mentioning
confidence: 59%
“…[11][12][13][14] We showed that γ-H2AX intensity in NK cells could be a more sensitive marker than T lymphocytes to evaluate early CMR-induced DNA damage. We also reported, for the first time, the dynamic evolution of DNA damage over long-time periods (≤1 month).…”
Section: Cmr Scanning and Dna Damage Of Circulating Lymphocytesmentioning
confidence: 99%
“…9,10 Several studies reported an immediate post-MRI increase of histone H2AX phosphorylation (γ-H2AX) in lymphocytes, a marker of DNA double-strand breaks, in a magnitude comparable with damages produced by low-dose ionizing radiation. [11][12][13] Whether MRI-induced DNA damage can persist or evolve over time is unknown. In this study, we sought to evaluate the early and late biological responses of blood cells (DNA double-strand breaks, cell count, cell death, and cell activation) to CMR in normal subjects.…”
mentioning
confidence: 99%
“…There are some studies on adverse health effects related to MRI (11)(12)(13)(14)(15)(16)(17)(18). Among the more recent work are two studies indicating a genotoxic potential of MRI in cell cultures (15;16).…”
Section: Introductionmentioning
confidence: 99%